Rapid binding to protofilament edge sites facilitates tip tracking of EB1 at growing microtubule plus-ends - Samuel J Gonzalez; Julia M Heckel; Rebecca R Goldblum; Taylor A Reid; Mark McClellan; Melissa K Gardner (eLife, 2024)
EB1 is a key cellular protein that delivers regulatory molecules throughout the cell via the tip-tracking of growing microtubule plus-ends. Thus, it is important to understand the mechanism for how EB1 efficiently tracks growing microtubule plus-ends. It is widely accepted that EB1 binds with higher affinity to GTP-tubulin subunits at the growing microtubule tip, relative to GDP-tubulin along the microtubule length. However, it is unclear whether this difference in affinity alone is sufficient to explain the tip-tracking of EB1 at growing microtubule tips. Previously, we found that EB1 binds to exposed microtubule protofilament-edge sites at a ~70 fold faster rate than to closed-lattice sites, due to diffusional steric hindrance to binding. Thus, we asked whether rapid protofilament-edge binding could contribute to efficient EB1 tip tracking. A computational simulation with differential EB1 on-rates based on closed-lattice or protofilament-edge binding, and with EB1 off-rates that were dependent on the tubulin hydrolysis state, robustly recapitulated experimental EB1 tip tracking. To test this model, we used cell-free biophysical assays, as well as live-cell imaging, in combination with a Designed Ankyrin Repeat Protein (DARPin) that binds exclusively to protofilament-edge sites, and whose binding site partially overlaps with the EB1 binding site. We found that DARPin blocked EB1 protofilament-edge binding, which led to a decrease in EB1 tip tracking on dynamic microtubules. We conclude that rapid EB1 binding to microtubule protofilament-edge sites contributes to robust EB1 tip tracking at the growing microtubule plus-end.